PERLINDUNGAN HUKUM TERHADAP USAHA KECIL MENENGAH (UKM) BERDASARKAN UU NO. 8 TAHUN 1999 TENTANG HUKUM PERLINDUNGAN KONSUMEN - Sri Yuliana (Fakultas Hukum Universitas IBA Palembang, 2022)
In Indonesia, SMEs have been the backbone of the economy for a long time. The number of SMEs until 2011 reached around 52 million. SMEs in Indonesia are very important to the economy as they contribute 60% of GDP and accommodate 97% of the workforce. However, access to financial institutions is very limited, only 25% or 13 million SMEs have access to financial institutions. The Government of Indonesia, fosters SMEs through the Office of Cooperatives and SMEs, in each province or district/city. It can be said that Small and Medium Enterprises or SMEs have an important role in the Indonesian economy. But all businesses including SMEs also have big challenges such as hiring the right people, building a brand and many others. And also challenges in terms of marketing the product. As a state of law, a state based on law (rule of law), the government should stipulate a basic concept that contains legal guidance on the direction of national law development for a certain period of government. The lack of protection makes Indonesian MSEs have difficulty in developing, unfortunately this fact is often misunderstood by the government, the business world and the community. However, its existence in the APBN structure often suffers from economic injustice, such as to meet the demand for disaster emergency response funds from the regions. The allocation of funds that should be used for the development of SMEs is requested to be allocated for flood disasters. This will make SMEs feel stepchildren in their own country. The role of government in market economies, especially in Asia, is very large and significant. The big challenge for the government's role for SMEs, apart from various internal obstacles, is the extent to which they create dependence on foreign economic intervention. Because avoiding foreign investment in the Indonesian economy is also something that is very unlikely in this era of globalization. But the idea of ​​developing SMEs, at least, can help the Indonesian economy to reduce dependence on foreign parties. To realize a strong national economy, SMEs need to be empowered so that they can become strong and independent and can develop.However, if it is manipulated, the government has long been providing guidance to small, medium-sized enterprises and cooperatives. The development of this business group since independence has undergone several changes. In the past, coaching for cooperatives was separated from coaching for small and medium enterprises. One is fostered by the Ministry of Cooperatives, while the other is fostered by the Ministry of Industry and the Ministry of Trade. After going through several changes, since the last few years the development of small, medium and cooperative businesses has been carried out under one roof under the Department of Cooperatives, Small and Medium Enterprises.